2011
DOI: 10.2147/oajsm.s22956
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ultra-triathlon performances

Abstract: Despite increased interest in ultra-endurance events, little research has examined ultra-triathlon performance. The aims of this study were: (i) to compare swimming, cycling, running, and overall performances in three ultra-distance triathlons, double Ironman distance triathlon (2IMT) (7.6 km swimming, 360 km cycling, and 84.4 km running), triple Ironman distance triathlon (3IMT) (11.4 km, 540 km, and 126.6 km), and deca Ironman distance triathlon (10IMT) (38 km, 1800 km, and 420 km) and (ii) to examine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 14 publications
2
39
2
1
Order By: Relevance
“…[3] Ultra-triathlons, consisting of distances greater than Ironman distance include double Ironman triathlons (7.6km swim, 360km cycle and 84 km run) and decaIronman triathlon (38km swim, 1800km cycle and 420 km run) also appeared during the 1980"s with the first double Ironman triathlon held in 1985 in Huntsville (USA). [4,5,6,7] More recently, in addition to conventional road based triathlon, off-road triathlon combining swimming, mountain biking and trail running has also established itself in the field of endurance sports, and has grown very rapidly in popularity. [8,9] Triathlon performance has been studied from numerous perspectives by a number of research groups over approximately the same period that the sport has grown.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Ultra-triathlons, consisting of distances greater than Ironman distance include double Ironman triathlons (7.6km swim, 360km cycle and 84 km run) and decaIronman triathlon (38km swim, 1800km cycle and 420 km run) also appeared during the 1980"s with the first double Ironman triathlon held in 1985 in Huntsville (USA). [4,5,6,7] More recently, in addition to conventional road based triathlon, off-road triathlon combining swimming, mountain biking and trail running has also established itself in the field of endurance sports, and has grown very rapidly in popularity. [8,9] Triathlon performance has been studied from numerous perspectives by a number of research groups over approximately the same period that the sport has grown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the distances differ enormously between the single competitions. Much more endurance, training, and mental strength is required for a successful finish in a Double Deca Iron ultra-triathlon than for the ten-times shorter Double Iron ultra-triathlon (Knechtle, Duff, Amtmann & Kohler 2008a, Knechtle, Schwanke, Knechtle, & Kohler 2008c, Knechtle, Knechtle, Rüst & Rosemann 2011a, Lepers, Knechtle, Knechtle & Rosemann 2011, Zaryski & Smith 2005. Thus, a Triple Iron ultra-triathlete has to train for more hours than an Ironman-triathlete to reach the same level of performance (Knechtle, Knechtle, Rüst, & Rosemann 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only a few ultra-triathletes of a very high level are able to complete an ultra-triathlon longer than a Triple Iron ultra-triathlon distance. The athletes often start with shorter distances (Lepers, Knechtle, Knechtle & Rosemann 2011). Therefore, the names of athletes who started a longer ultra-triathlon distance already appeared on the ranking lists of previous Double Iron ultra-triathlons and Triple Iron ultra-triathlons (www.iutasport.com).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes require special characteristics in anthropometry (Hoffman, 2008 Besides the aspects of training and race preparation, characteristics of both anthropometry and physiology as well as the nationality of an athlete could also have an influence on the outcome of the performance in an endurance race (Larsen, 2003;Lepers et al, 2011;Rüst et al, 2012b). Regarding the origin of runners, Larsen (2003) reported that in the last two decades a change in the dominance of middle and long-distance running events occurred.…”
Section: Introductionmentioning
confidence: 99%